2014
DOI: 10.18497/iejee-green.53452
|View full text |Cite
|
Sign up to set email alerts
|

Using Social Media to Reinforce Environmental Learning and Action Taking for School Students

Abstract: Environmental experiences often engage learners and create an intention to act, which is then not followed through once the learner is removed from the environment. This study utilized an exploratory, interpretive framework with younger primary school classes to investigate if transfer of learning from field trip experiences in and about the environment into action for the environment could be reinforced by social media interaction between the environmental educator and the class through a blog. Field observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…For example, the follow-up online survey we conducted four months after participants' initial visit to the website showed that, while knowledge may have been retained and even built on for those community members who had voluntarily revisited the website, the lack of post-learning experience reinforcement had led to less reported action on the issue than we had hoped for. This signals the need for more intense reinforcement (Ballantyne & Packer, 2011) after such learning experiences; we posit that social media, had they been better developed at the time of the study, would have potentially enabled that reinforcement (Wals, 2015;Warner et al, 2014). In future interventions, this may more readily bring about the sort of transformative change within communities which is required for longterm effectiveness (Fien & Tilbury, 2002;Räthzel & Uzzell, 2009;Sterling, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…For example, the follow-up online survey we conducted four months after participants' initial visit to the website showed that, while knowledge may have been retained and even built on for those community members who had voluntarily revisited the website, the lack of post-learning experience reinforcement had led to less reported action on the issue than we had hoped for. This signals the need for more intense reinforcement (Ballantyne & Packer, 2011) after such learning experiences; we posit that social media, had they been better developed at the time of the study, would have potentially enabled that reinforcement (Wals, 2015;Warner et al, 2014). In future interventions, this may more readily bring about the sort of transformative change within communities which is required for longterm effectiveness (Fien & Tilbury, 2002;Räthzel & Uzzell, 2009;Sterling, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…Social media has become an important tool for providing a space and means for the public to participate in influencing or disallowing environmental decisions made by governments and corporations that affect all. This has developed a mode for people to be connected with local environmental challenges and interpretations to larger-scale stories that will affect the global community (Warner, Eames & Irving, 2014) Undermining of community participation by politicians…”
Section:  154mentioning
confidence: 99%
“…This education outside the classroom (EOTC) can then be aligned with formal curriculum guidelines. For example, in the case of this study, it can meet the objectives of The New Zealand Curriculum (Ministry of Education 2007) around science and sustainability within the local environment, which can lead to the development of student ecoliteracy (Ministry of Education 2016; Warner, Eames, and Irving 2014).…”
Section: Introductionmentioning
confidence: 99%